Examination of the development and aging of brain deactivation using a unimanual motor task. (18th July 2021) - Morita, Tomoyo; Asada, Minoru; Naito, Eiichi
Abstract : In the central nervous system, regional neuronal inhibition plays important roles in functional segregation. Here, we showed how brain deactivation, which is a putative index of neuronal inhibition, develops and ages using a unimanual motor task. Healthy right-handed children (8–11 years), adolescents (12–15 years), young adults (20–24 years), and older adults (69–75 years; 21 participants in each group) underwent functional magnetic resonance imaging with their eyes closed while they performed 1-Hz alternating extension–flexion of the right wrist. In young adults, we found deactivations in the hand/arm section of the ipsilateral primary sensorimotor cortices (SM1) including the dorsal premotor cortex (interhemispheric inhibition), foot and face SM1 sections (cross-somatotopic inhibition), visual and auditory cortices (cross-modal inhibition), and precuneus and medial prefrontal cortex of the default mode network (DMN; DMN inhibition). Interhemispheric, cross-modal, and DMN inhibitions developed from childhood to adulthood, but cross-somatotopic inhibition showed no developmental changes. Conversely, interhemispheric, cross-somatotopic, and cross-modal inhibitions, but not DMN inhibition, decreased with aging. Thus, neuronal inhibition generally progresses with development and deteriorates with aging, with some noted regional differences. This was the first study to systematically describe the development and aging of brain deactivation, which may reflect regional neuronal inhibition. GRAPHICAL ABSTRACT: UF0001